Evaluasi Implementasi Anggaran Belanja Sebagai Sarana Pertanggungjawaban Pelaksanaan APBD - Pamungkas, Bambang (Jurnal Ilmiah Akuntansi Kesatuan, 2013)
State and public budget is a compass of action that will be implemented by government comprising revenues, expenditures, and transfer scheme, as well as financing measured by rupiah, arranged systematically in one period based on a certain classification. It can be meant as a document representing financial condition of an organization (government) in point of revenues, expenditures, and activities. The accountability of APBD implementation is defined as a part of regional financial management as well as a part of budget process. Thereby, the accountability of APBD implementation is a form of regional government’s obligation to carry out financial management in an orderly manner, following rule of law, efficient, economical, selective, transparent, and paying attention to sense of justice and fairness. The purpose of this research is to evaluate the implementation of budget at a government service having to account for the realization of budget utilization which has been used by related offices to the central government, and to know how far the accuracy of budget utilization accountability will be. The research was conducted by the writer at Dinas Bina Marga & Pengairan located in Bogor Regency. Dinas Bina Marga & Pangairan – Bogor Regency operates in public services in the field of road maintenance (as well as highway construction) and waters. The result of this research shows that Dinas Bina Marga & Pengairan – Bogor Regency has accounted for budget implementation well enough. The budget realization that has been used by Dinas Bina Marga & Pengairan – Bogor Regency can be accounted for enough to be a basis of budget calculation. Its value is as presented in the balance sheet. The costs which are taken into account in budget is actual costs in the period. To comform the cost alocation accuracy, the right cost realization has a mark-A. It’s alocated based on percentage from the level of activities in services to society that’s in proportion to total activities of all sevices existing at Dinas Bina Marga & Pengairan – Bogor regency. The evaluation result of of this research shows that there are several things which are slipped away from budget calculation done by Dinas Bina Marga & Pengairan – Bogor Regency, among other things is the fact that SPJ reporting was often late due to technical factors in the field with the result that it’s happened financial reporting slowness. Besides that, there has not been computerization accounting system yet in financial statement. Considering that there are many activities dealt with by Dinas Bina Marga & Pengairan – Bogor Regency, it causes supervision cannot be optimal. By accounting computerized, all processes in financial statement arrangement and supervision by the official in implementing budget can be optimized.